Communism and Hunger: Preface - From the Guest Editors (East/West: Journal of Ukrainian Studies, 2016)
Over the past two decades, researchers have made significant progress in studying the great political famines of the twentieth century. As a result of increased access to formerly closed archives and the collective efforts of the international scholarly community, we now have a rather accurate picture of the causes, dynamics, demographic impact, and consequences of the pan-Soviet famines of 1931-33, the Ukrainian Holodomor, the Kazakh great hunger, and the terrible famine of 1959-61 in China produced by the Great Leap Forward...